Intracranial Dural Arteriovenous Fistulas: A Systematic Approach—Diagnosis, Classification, and Endovascular Treatment - Sammoud, Skander; Hammami, Nadia (The Arab Journal of Interventional Radiology, 2023)
Intracranial dural arteriovenous fistulas (DAVFs) are rare lesions accounting for 10 to 15% of intracranial arteriovenous malformations. They involve an anomalous shunt between meningeal arteries, intracranial (venous sinuses and/or cortical veins), or medullary veins. The DAVFs are usually acquired, implying previous aggression of the dura mater. Thus, they are associated with dural sinus thrombosis, previous craniotomy, and trauma. However, they are idiopathic in most instances and have no evident cause. Their clinical presentation is variable, with symptoms depending on their location and venous drainage pattern. However, lesions with cortical venous drainage have the highest risk of causing the most significant morbidity and mortality. High clinical suspicion alongside noninvasive cross-sectional imaging techniques such as computed tomography and magnetic resonance imaging help establish the diagnosis. Digital subtraction angiography is the gold standard for diagnosis and accurate classification, permitting the evaluation of the feeding vessels, cortical venous drainage, and venous ectasia. Accordingly, a prompt diagnosis and precise classification of these lesions are essential. Endovascular treatment is nowadays the primary therapeutic modality for DAVFs. The access route can be divided into transarterial, transvenous, and combined approaches based on angioarchitecture, venous drainage model, and location. Surgical resection and stereotactic radiosurgery may be considered in some cases. A personalized case-by-case approach accomplishes a high complete treatment grade with a low complication rate. This review highlights the epidemiology, pathogenesis, clinical presentation, classification, diagnosis, and endovascular treatment of patients with intracranial DAVFs.
Keywords: angiogram; arteriovenous fistulas; dural; embolic agent; embolization